The application of sinusoidal blade-leading edges in a fan-design methodology to improve stall resistance. (May 2014) - Corsini, Alessandro; Delibra, Giovanni; Sheard, Anthony G
Taking inspiration from previous biomimetic studies on the performance of humpback whale flippers, this paper reports a programme of work to design a 'whale-fan' that incorporates a sinusoidal leading-edge blade profile that mimics the tubercles on humpback whales flippers. Previous researchers have used two-dimensional cascades of aerofoils to study the effects of a sinusoidal profile on aerofoil lift and drag performance. The research was primarily concerned with elucidating the fluid-flow mechanisms induced by the sinusoidal profile and the impact of those mechanisms on aerofoil performance. The results indicate that a sinusoidal leading-edge profile has improved lift recovery post-stall and, thus, is inherently more aerodynamically resistant to the effect of stall. The reported research focuses on the application of previous research conducted with infinite span cascades of aerofoils to the design and optimisation of a finite span aerofoil. The paper presents the assumptions when developing a three-dimensional aerofoil-design methodology that correlates the sinusoidal profile of the blade-leading edge with the desired vorticity distribution at the trailing edge. The authors apply the developed methodology to the design of a fan blade's tip region to control separation at the trailing edge. The paper presents numerically derived whale-fan performance characteristics and compares them with both numerically and experimentally derived performance characteristics of the baseline fan.